Perancangan Sistem Informasi Desa (SID) pada Desa Bungko Kecamatan Kotamobagu Selatan - Siska Ayu Widiana; Firdaus, Iqbal; Supriyanto Supriyanto (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to design and implement a Village Information System (SID) in Bungko Village, Kotamobagu Selatan District, to improve administrative efficiency and public services. The developed system enables village officials to manage population data, process service requests, and generate financial reports more quickly and organized. Village residents can also access services online, submit requests, and easily monitor the status of their services. The SID implementation uses web-based technology, including PHP, and MySQL, ensuring data security and reliability. The results of this study show that the SID can enhance transparency, efficiency, and accountability in village governance. However, improving technology infrastructure, user training, and integration with other systems are essential for further development. This study is expected to serve as a model for other villages in implementing technology to advance administration and public services.